Excavation at the 'Tree of Life' site - Mearaj, Mohammed Redha Ebrahim Hasan (Proceedings of the Seminar for Arabian Studies, 2012)
The 'Tree of Life' is an iconic location in south central Bahrain, about 40 km south of the capital al-Manāmah and about 2 km inland from the east coast near the settlement of Jaww. The mesquite tree grows on top of an archaeological tell, about 10 m above sea level. This paper covers excavations at the site conducted between April and July 2010 by a Bahraini team from the Ministry of Culture, Bahrain. Before excavation it was recognized by the dressed stones and remnants of limestone walls evident in the tell that the site contained a significant settlement. Surface finds of pottery indicated a late Islamic period site. Excavation revealed a range of finds, including complete pots, placed upside down and supported vertically by small stones placed between them. Light-coloured gypsum was used in the walls and for plaster floors. One series of pots contained evidence suggesting the production of wood tar or creosote at the site. This is unique in Bahrain. The excavations at the Tree of Life have produced significant evidence of a range of activities in a late medieval Islamic settlement in Bahrain.